Association of Use of Rehabilitation Services With Development of Dementia Among Patients With Rheumatoid Arthritis: Analysis of Domestic Data in Taiwan - Lu, Ming-Chi; Livneh, Hanoch; Yen, Chieh-Tsung; Huang, Hua-Lung; Lin, Miao-Chiu; Yen, Shu-Wen; Lai, Ning-Sheng; Tsai, Tzung-Yi (Frontiers in Medicine, 2020)
Objectives. People with rheumatoid arthritis (RA) have increased risk of developing dementia. It remains unclear whether the use of rehabilitation services (RS) can reduce this risk. This retrospective cohort study aimed to determine the association of rehabilitation services (RS) use with the development of dementia among individuals with RA. Methods. A national health insurance database was used to identify 2,927 newly diagnosed patients with RA, 20-70 years, between 1998 and 2007. Among them, 965 received RS, and 1,962 patients who did not receive RS (non-RS users). All enrollees were followed until the end of 2012 to record incident cases of dementia. A Cox proportional hazards regression model was used to compute adjusted hazard ratios (aHR) for the relationship of RS use with dementia. Results. During the study period, 388 RS users and 1,224 non-RS users developed dementia, corresponding to incidence rates of 75.46 and 115.42 per 1,000 person-years, respectively. Use of RS was significantly associated with a lower risk of dementia (aHR= 0.60; 95% confidence interval [CI]= 0.53-0.67). Those who used the high intensity of RS (≧15 courses) had the greatest benefit (aHR= 0.38; 95% CI= 0.40-0.55). Conclusions. Integrating RS into the clinical management for patients with RA may decrease their risk of developing dementia.